Regulated Monosyllabic Talk Test vs. Counting Talk Test During Incremental Cardiorespiratory Exercise: Determining the Implications of the Utterance Rate on Exercise Intensity Estimation - Mahmod, Siti Ruzita; Narayanan, Leela T.; Abu Hasan, Rumaisa; Supriyanto, Eko (Frontiers in Physiology, 2022)
Purpose: When utilizing breathing for the purpose of speech, the rate and volume of inhalation as well as the rate of exhalation during the utterance seem to be largely governed by the speech-controlling system and its requirements with respect to phrasing, loudness, and articulation. However, since the Talk Test represents a non-standardized form of assessment of exercise intensity estimation, this study aimed to compare the utterance rate and the estimated exercise intensity using a newly introduced time-controlled monosyllabic Talk Test (tMTT) versus a self-paced Counting Talk Test (CTT) across incremental exercise stages and examined their validity. Methods: Twenty-four participants, 10 males and 14 females (25 ± 4.0 yr; 160 ± 10 cm; 62 ± 14.5 kg) performed two sessions of submaximal cardiorespiratory exercise at incremental heart rate reserve (HRR) stages ranging from 40% to 85% of HRR: one session was performed with a currently available CTT that was affixed to a wall in front of the participants, and the other session was conducted with a tMTT with a 1-s inter-stimulus interval that was displayed from a tablet. In each session, the participants performed six stages of exercise at 40%, 50%, 60% 70%, 80% and 85% HRR on a treadmill and were also asked to rate their perceived exertion based on Borg’s 6 to 20 Rating of Perceived Exertion (RPE) at each exercise stage. Results: The newly designed tMTT significantly delineated all the six stages of incremental exercise (p ≤ 0.017), while CTT could only delineate exercise stages at 60%, 80%, and 85% HRR. However, in estimations of exercise intensity, the tMTT demonstrated only moderate concurrent validity with HRR and Borg’s RPE like the CTT. Conclusion: If the purpose of exercise monitoring is to detect the intensity of light, moderate, and vigorous exercise intensity, the tMTT could be more universally applicable. However, due to its larger variability of speech rate across exercise intensities, the time-regulated approach may alter the speech breathing characteristics of the exercising individuals in other ways that should be investigated in future research.